Introduction to Infectious Diseases in Hard Clams - Shirley Baker; Denise Petty; Ruth Francis-Floyd; Roy Yanong; Leslie Sturmer (EDIS)
FA125, a 7-page illustrated fact sheet by Shirley Baker, Denise Petty, Ruth Francis-Floyd, Roy Yanong, and Leslie Sturmer, familiarizes clam growers with common clam diseases. Includes glossary of terms and resources for further reading. Published by the UF Department of Fisheries and Aquatic Sciences, October 2006.